Taxonomic diversity, niche width and similarity in the use of plant resources by bees (Hymenoptera: Anthophila) in a cerrado area - Andena, Sergio R.; Santos, Eduardo F. [UNESP]; Noll, Fernando Barbosa [UNESP] (Taylor & Francis Ltd, 2012)
Most of the studies on the bee fauna of cerrado have shown incomplete approaches, focusing on species diversity or on a fraction of the assemblage. This work presents similarities among bee species based on visited plants and also shows taxonomic diversity of bees for plant resource sets offered by species in a cerrado area (Pe-de-Gigante), one of the few conservation areas of cerrado in the São Paulo State, Brazil. A total of 737 specimens, belonging to 71 bee species, were collected visiting 52 plant species. Species clusters based on visited plants show that species of Epicharis, for example, are more similar among themselves than from species of other genera. In addition, bee assemblage showed a nested structure, indicating the presence of specialist species exploiting resources subsets used by generalist species under strong intra-specific and weak inter-specific competitions.
Keywords: bee; Cerrado; Pe-de-Gigante; ecology; Diversity